Robust integral back-stepping control for a quadrotor: experiments and simulation. (2018) - Cardimen, Scott; Zohdy, Mohamed A.; Sababha, Moath; Rusek, Andrew
This paper presents a robust integral back-stepping (RIB) control method applied to a constructed quadrotor prototype. The controller provides stabilisation of attitude and motion under various assumptions. The controller is robust to reject external disturbances and compensate for potential parameter uncertainties. An analysis of the benefits of the proposed control method is presented by comparison to classic linear control methods. This analysis is supported by simulation and implementation on a physical prototype. The simulation parameters match that of the prototype to provide a consistent means of validation.